To determine whether Izzie solved the inequality correctly, let's go through her steps.
Starting with the original inequality: \[ 3(t+1) - 4t \geq -5 \]
-
Distributing the \(3\): \[ 3t + 3 - 4t \geq -5 \]
-
Combining like terms: \[ -t + 3 \geq -5 \]
-
Subtracting \(3\) from both sides: \[ -t \geq -8 \]
-
To solve for \(t\), multiply both sides by \(-1\). Remember that multiplying or dividing by a negative number reverses the inequality: \[ t \leq 8 \]
So the correct solution is: \[ t \leq 8 \]
Izzie concluded that \(t \geq 8\), which is incorrect. Therefore, her final answer is not correct.
In response to the statement "Izzie should not have changed the inequality symbol from ≥ to ≤":
- This statement is True. She made an error when changing the direction of the inequality after multiplying both sides by \(-1\).
So the answer to the original question is False, as Izzie did not solve it correctly and should have reversed the inequality symbol.